A novel Orf virus D1701-VrV-based Dengue virus (DENV) vaccine candidate expressing HLA-specific T cell epitopes: a proof-of-concept study - Reguzova, Alena; Fischer, Nico; Müller, Melanie; Salomon, Ferdinand; Jänisch, Thomas; Amann, Ralf (Biomedicines, 2021)
Although dengue virus (DENV) affects almost half of the world’s population there are neither preventive treatments nor any long-lasting and protective vaccines available at this time. The complexity of the protective immune response to DENV is still not fully understood. The most advanced vaccine candidates focus specifically on humoral immune responses and the production of virus-neutralizing antibodies. However, results from several recent studies have revealed the protective role of T cells in the immune response to DENV. Hence, in this study, we generated a novel and potent DENV vaccine candidate based on an Orf virus (ORFV, genus Parapoxvirus) vector platform engineered to encode five highly conserved or cross-reactive DENV human leukocyte antigen (HLA)-A*02- or HLA-B*07-restricted epitopes as minigenes (ORFV-DENV). We showed that ORFV-DENV facilitates the in vitro priming of CD8+ T cells from healthy blood donors based on responses to each of the encoded immunogenic peptides. Moreover, we demonstrated that peripheral blood mononuclear cells isolated from clinically confirmed DENV-positive donors stimulated with ORFV-DENV generate cytotoxic T cell responses to at least three of the expressed DENV peptides. Finally, we showed that ORFV-DENV could activate CD8+ T cells isolated from donors who had recovered from Zika virus (ZIKV) infection. ZIKV belongs to the same virus family (Flaviviridae) and has epitope sequences that are homologous to those of DENV. We found that highly conserved HLA-B*07-restricted ZIKV and DENV epitopes induced functional CD8+ T cell responses in PBMCs isolated from confirmed ZIKV-positive donors. In summary, this proof-of-concept study characterizes a promising new ORFV D1701-VrV-based DENV vaccine candidate that induces broad and functional epitope-specific CD8+ T cell responses.
Gesehen am 24.02.2022